SPORT-RECREATIONAL CONTESTS MARKETING AND PROMOTION IN MONTENEGRO’S TOURISM DEVELOPMENT - Rajak, Bojan; Marjanović, Ranko; Marijanović, Stefan; Klarić, Dragan (Scientific Journal Management in Sports, 2014)
The paper presents the current state of sports content promoted tourism in Montenegro. Particular importance was given NTOCG web site, currently the largest database of sports and recreational facilities in tourism in Montenegro. In addition on the basis of compara- tive analysis for 2012.and 2013.work contains statistical data on the number of sport and recreation in Montenegro’s tourism for all three regions separately (Northern, Central and Southern).